Bad Jobs as a Core Driver of Growing Social Inequality in the United States - Tatiana Karabchuk (Экономическая социология, 2015)
This is a review of a masterpiece by a famous professor of labor sociology. Anyone looking for understanding current labor market processes needs to read this latest work by Arne L. Kalleberg, the Kenan Distinguished Professor of Sociology at the University of North Carolina at Chapel Hill. Kalleberg focuses on the US and shares his deep understanding of a wide range of social and economic mechanisms of the labor market under globalization. The book gives a vivid description of the current labor market and provides an explanation for the changes that brought about the rise of precarious employment. The book sheds light on the reasons for the dramatic increase in polarization and inequality between jobs and both between and within occupations. Kalleberg argues that the US is in dire need of a new social contract to tackle the challenges that arise from a globalized division of labor, widening polarization in the quality of jobs, and the proliferation of precarious work. An example of such a new social contract is a “flexicurity” system, aspects of which exist today in some countries. Kalleberg claims that only a coordinated effort by government, business and labor can address the sources and consequences of the polarization in job quality and that only such an effort will be able to improve both the economic competitiveness of the US and the quality of jobs and lives of American citizens. Though the book itself is focused on the American labor market during the last forty years, this review attempts to place Kalleberg’s ideas into a global context.